Semiconductor Research Experimental Techniques - Patane, Amalia; Balkan, Naci.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The book describes the fundamentals, latest developments and use of key experimental techniques for semiconductor research. It explains the application potential of various analytical methods and discusses the opportunities to apply particular analytical techniques to study novel semiconductor compounds, such as dilute nitride alloys. The emphasis is on the technique rather than on the particular system studied.
Electron Diffraction: RHEED and LEED -- Transmission Electron Microscopy and Energy-Dispersive X-ray Spectroscopy -- Techniques for Surface Characterization -- Optical Modulation Spectroscopy -- Photoluminescence and Magnetophotoluminescence -- High Pressure Studies -- Microphotoluminescence, Scanning Near-Field Optical Microscopy and Cathodoluminescence -- Time Resolved Optical Spectroscopy -- Raman Spectroscopy -- Cyclotron Resonance -- Transport in High Magnetic Fields -- Photoconductivity -- Hot Carrier Transport.
Keywords: Physics; Semiconductors; Physical measurements; Measurement; Optics; Optoelectronics; Plasmons (Physics).; Spectroscopy; Microscopy; Electrical engineering; Optical materials; Electronic materials; Physics; Semiconductors; Spectroscopy and Microscopy; Optical and Electronic Materials; Electrical Engineering; Measurement Science and Instrumentation; Optics, Optoelectronics, Plasmonics and Optical Devices; Electronic books